2015
DOI: 10.1103/physrevb.92.125154
|View full text |Cite
|
Sign up to set email alerts
|

NMR evidence for an intimate relationship between antiferromagnetic spin fluctuations and extendeds-wave superconductivity in monocrystallineSrFe2(As1x

Abstract: We report systematic 31 P-NMR study on iron (Fe)-based superconductors SrFe2(As1−xPx)2 (Sr122AsP), in which a superconducting (SC) transition temperature Tc at x=0.35 increases from Tc=26 K up to 33 K by annealing an as-grown mono-crystalline sample. The present NMR study has unraveled that Tc reaches a highest value of 33 K at x=0.35 around a quantum critical point at which antiferromagnetic (AFM) order disappears. When noting that the SC transition disappears at x=0.6 where the AFM spin fluctuations (SFs) ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
(54 reference statements)
2
6
0
Order By: Relevance
“…Here, note data at temperatures higher than T ∼160 are used the contribution of AFMSFs in (1/T 1 ) is negligible. The value of K chem is comparable to those evaluated in previous 10,16 K s (T is proportional to χ(q=0) the s = A hf (0)χ(q=0) ∝ A hf (0)N (E F ). Here, χ(q=0) is the static spin susceptibility, A hf (0) is the hyperfine coupling constant at q=0, and N (E F ) is the density of states (DOS) at the Fermi level (E F ).…”
Section: Scsupporting
confidence: 86%
See 2 more Smart Citations
“…Here, note data at temperatures higher than T ∼160 are used the contribution of AFMSFs in (1/T 1 ) is negligible. The value of K chem is comparable to those evaluated in previous 10,16 K s (T is proportional to χ(q=0) the s = A hf (0)χ(q=0) ∝ A hf (0)N (E F ). Here, χ(q=0) is the static spin susceptibility, A hf (0) is the hyperfine coupling constant at q=0, and N (E F ) is the density of states (DOS) at the Fermi level (E F ).…”
Section: Scsupporting
confidence: 86%
“…This contrasted behavior between (1/T 1 T ) and K s (T ) demonstrates the development of AFMSFs with finite wave vectors as temperature decreases. To deduce the development of AFMSFs following the previous studies, 8,10,16 we assume that (1/T 1 T ) is decomposed as…”
Section: Scmentioning
confidence: 99%
See 1 more Smart Citation
“…31 K ab is the sum of the spin shift K spin and the chemical shift K chem , that is 31 K ab = K spin + K chem . The chemical shift K chem is estimated to be 0.018 % for BaFe 2 (As 1−x P x ) 2 [10] and 0.04 % for SrFe 2 (As 1−x P x ) 2 [11]. Then, K spin is estimated to be 0.10 or 0.12 %.…”
Section: Resultsmentioning
confidence: 99%
“…In the underdoped regime with respect to the P concentration for BaFe 2 (As 1−x P x ) 2 , NMR measurements revealed that the superconductivity emerges in the weakly antiferromagnetic state at T c < T N [9]. Systematic 31 P NMR studies have been performed for BaFe 2 (As 1−x P x ) 2 [10] and SrFe 2 (As 1−x P x ) 2 [11]. The successive phase transitions from spin-density-wave (SDW) antiferromagnets to unconventional superconductors (T c < T N ) have been studied with theoretical models [12,13].…”
Section: Introductionmentioning
confidence: 99%